A comparative analysis of interferons and direct‐acting antivirals on the expression of genes involved in hepatitis C pathogenesis. Issue 11 (16th August 2020) - Farooq, Mariya; Rauf, Mahd; Tahir, Fatima; Manzoor, Sobia
Abstract: The discovery of direct‐acting antivirals (DAAs) has revolutionized the treatment of hepatitis C worldwide. In contrast, pegylated interferon‐alpha (PEG IFN‐α), the older regimen, had limited success. However, the effect of DAAs on the expression of immunomodulatory genes involved in liver pathologies remains ambiguous. The objective of this study was to explore and contrast the effects of DAAs and PEG IFN‐α on the expression of selected immunomodulatory genes. Fifty individuals were enrolled in the study and they were divided into five categories; healthy individuals, treatment‐naive, DAAs‐responders, DAAs‐nonresponders, and interferon‐relapsers. The effect of the therapies on the expression of transforming growth factor‐beta (TGF‐β), tumor necrosis factor‐alpha (TNF‐α), suppressor of cytokine signaling 3 (SOCS‐3), copper/zinc superoxide dismutase (Cu/Zn SOD), interleukin 10 (IL‐10), and collagen type 1 was analyzed. Expression analysis of the selected genes was done through real time polymerase chain reaction. A significantly increased expression of TGF‐β was observed in the patients who received DAAs or PEG IFN‐α, which suggests that patients receiving anti‐HCV therapies are prone to developing fibrosis. Moreover, DAAs‐nonresponders had higher expression of TNF‐α, SOCS‐3, and IL‐10. The elevated expression of TNF‐α and SOCS‐3 insinuates that DAAs‐nonresponders may develop insulin resistance and steatosis in the future. Finally, in addition to TGF‐β, high expression of collagen was found in interferon relapsers, which suggests that these patients are the most susceptible to developing cirrhosis. Highlights: In the following study the effect of direct‐acting antivirals (DAAs) on the genes involved in hepatitis C pathogenesis is investigated and compared with the effect of interferons on these genes. A significantly increased expression of transforming growth factor beta (TGF‐β) was observed in all the patients who received DAAs or interferons, suggesting that patients receiving anti‐HCV therapies are prone to developing fibrosis. An elevated expression of tumor necrosis factor‐alpha (TNF‐α) and suppressor of cytokine signaling 3 (SOCS‐3) was observed in DAAs‐nonresponders, which insinuates that they could develop insulin resistance and steatosis in the future. Finally, a high expression of TGF‐β and collagen was observed in interferon‐relapsers, which indicates that this cohort is susceptible to cirrhosis.